"He Must Learn What Being a Man is All About": Negotiating the Male Code at the Louisiana State Penitentiary. Issue 2 (1st February 2016) - Kennedy, Liam
Abstract: Much of what has been written about masculinities inside prisons focuses on the pressure to live up to a hypermasculine ideal that privileges aggression, the concealment of vulnerability, and the victimization of weaker inmates. Believing this approach lacks nuance, I explore how prisoners writing in The Angolite, the Louisiana State Penitentiary's prison newsmagazine, conceive of manhood. Incorporating hundreds of men's voices into this discussion reveals the complexity of these prisoners' lives as men—their emotional depth, friendships, and struggles to grow, learn, and better themselves—and compels us to reconsider what we think goes on inside prisons.